Carbon Dioxide Mediated Cellulose Dissolution and Derivatization to Cellulose Carbonates in a Low-pressure System - Chen-Gang Wang; Ning Li; Gang Wu; Ting Ting Lin; Agnes Mei Xian Lee; Shuo-Wang Yang; Zibiao Li; Dr. He-Kuan Luo (Carbohydrate Polymer Technologies and Applications, 2022)
An effective switchable solvent system using carbon dioxide (CO2) and 2-tert-butyl-1,1,3,3-tetramethylguanidine (BTMG) for cellulose dissolution and derivatization was developed. High concentration cellulose solution (up to 10 wt%) could be achieved by dissolving microcrystalline cellulose rapidly, within 5 min, into DMSO in presence of BTMG and 1 atm CO2 at room temperature. The cellulose-carbonate anion intermediate was characterized by 1H and 13C NMR spectroscopies, emphasizing the generation of cellulose carbonate anions and protonated BTMG. Addition of organochlorides into the cellulose solution triggers a nucleophilic substitution with cellulose-carbonate anions, producing various cellulose benzyl carbonates and a cellulose-carbonate-ester with degree of substitution (DS) up to 1.83 at 1 atm CO2 pressure and room temperature. The activation energy (Ea) and Gibbs free energy change (ΔG) of CO2-mediated dissolution and nucleophilic substitution were calculated by density functional theory. The results showed that the nucleophilic substitution is the rate-limiting step.